Optimised Extraction and Purification of Dual-Function Cosmetic-Grade Phycocyanin and Allophycocyanin from Dried Arthrospira platensis Biomass Using Conventional Methods - Ugnė Krakauskaitė; Shahana Aboobacker; Vaida Kitrytė-Syrpa; Michail Syrpas (Applied Sciences)
Arthospira platensis is a filamentous cyanobacterium considered an important source of phycobiliproteins (PBP), a class of water-soluble pigments with a wide range of applications. Although several extraction and purification techniques of PBP have been reported, there is still a need for strategies that achieve a balance between simplicity, cost-effectiveness, and scalability. To address this need, this study systematically evaluated conventional extraction methods—homogenisation, freeze–thaw cycles, and maceration. Maceration showed the best balance between yield purity and recovery among the tested techniques, and under optimal conditions (three cycles, 2 h/cycle, 0.1 M phosphate buffer), 55.9 mg/g of biomass of phycocyanin (PC) and 24.9 mg/g of biomass of allophycocyanin (APC) with notable antioxidant capacity (Folin-Ciocalteu’s and ABTS●+ assays) were yielded. Among the tested purification techniques, ammonium sulphate fractionation achieved a purity of 2.3 with recoveries of 92.9% and 79.9% for PC and APC, respectively, while purification with 0.5% activated carbon resulted in an extract purity of 2.5 and recoveries of 90.9% (PC) and 87.2% (APC). The suggested procedures could be considered a fast and cost-effective way to obtain cosmetic-grade PBP, thus offering an accessible solution for industries prioritising sustainable and economically viable production pipelines.